THE IMPACT OF ORGANIZATIONAL COMMITMENT, KNOWLEDGE, OHS MANAGEMENT, SAFETY CITIZENSHIP BEHAVIOR ON SAFETY PERFORMANCE OF PATIMBAN TOLL ROAD ACCESS PROJECT - Siswanto, Eko; Amin, Mawardi (Applied Research on Civil Engineering and Environment (ARCEE), 2025)
The construction industry in Indonesia, including the Patimban Toll Road Access project, faces safety challenges due to high accident rates, unsafe working conditions, and hazardous work environments. The high accident rate, as evidenced by 2,971 accidents in 2023, highlights the urgent need for enhanced implementation of OHS standards. This study focuses on key factors influencing safety performance at the Patimban Toll Road Access project, including organizational commitment, OHS management, knowledge management, and safety citizenship behavior. This study aims to examine the influence of organizational commitment, knowledge management, and occupational health and safety management (K3) on Safety Citizenship Behavior (SCB) and safety performance in the Patimban Toll Road Access project. The research also explores the mediating role of knowledge management, K3 management, and SCB in these relationships. A quantitative causal research approach was used, involving 98 direct workers from the Patimban Toll Road Access project. Data were collected through questionnaires and analyzed using Partial Least Squares (PLS) with the aid of SmartPLS 3.0. The results show that organizational commitment has a positive and significant effect on knowledge management and K3 management. Both knowledge management and K3 management positively influence SCB, which in turn contributes to improved safety performance. Furthermore, knowledge management and K3 management were found to significantly mediate the relationship between organizational commitment and SCB, as well as between SCB and safety performance. These findings suggest that effective knowledge management and K3 practices not only enhance safety citizenship behavior but also improve overall safety performance in the Patimban Toll Road Access project.